DEPENDENCE ON SHRINKAGE AND SWELLING IN CHEMICAL COMPOSITION AND ANATOMICAL STRUCTURE – AN OVERVIEW (Innovation in Woodworking Industry and Engineering design, 2026)
When the water content changes, the wood undergoes serious changes in its dimensions and volume. The processes of shrinkage and swelling are mutually reciprocal and associated with large energy changes in the different directions of the stem. These changes are due to the fact that wood is formed from polymers that contain hydroxyl groups. Dimensional changes during drying of raw wood begin when the water content falls below the fibre saturation point. Shrinkage is different for different wood species. Shrinkage is also different in different directions of the wood. The article examines research conducted on different wood species and at different levels of the chemical composition and anatomical structure of the wood, with the aim of explaining the processes of drying and swelling.